2022
DOI: 10.1007/s00018-022-04450-8
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin rescues SMA phenotypes in patient-derived cells and animal model

Abstract: Spinal muscular atrophy (SMA) is a genetic disease resulting in the loss of α-motoneurons followed by muscle atrophy. It is caused by knock-out mutations in the survival of motor neuron 1 (SMN1) gene, which has an unaffected, but due to preferential exon 7 skipping, only partially functional human-specific SMN2 copy. We previously described a Drosophila-based screening of FDA-approved drugs that led us to discover moxifloxacin. We showed its positive effect on the SMN2 exon 7 splicing in SMA patient-derived sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Surprisingly, these observations are different from studies generated with hiPS-derived MNs from SMA patients [79][80][81]. In their study, the authors observed a 50% loss of survival of MNs after 8 weeks in culture.…”
Section: Spinal Muscular Atrophycontrasting
confidence: 64%
“…Surprisingly, these observations are different from studies generated with hiPS-derived MNs from SMA patients [79][80][81]. In their study, the authors observed a 50% loss of survival of MNs after 8 weeks in culture.…”
Section: Spinal Muscular Atrophycontrasting
confidence: 64%
“…The second drug we have selected is moxifloxacin, a quinolone broad-spectrum antimicrobial that treats adults (≥ 18 years of age) suffering from respiratory tract infections, both upper and lower [ 29 ], as well as acute sinusitis [ 30 ], acute exacerbations of chronic bronchitis [ 31 ], community-acquired pneumonia [ 32 ], and skin and soft tissue infections [ 33 ]. Januel et al [ 34 ] studied the use of moxifloxacin to treat the genetic disorder spinal muscular atrophy (SMA). However, Inada et al [ 35 ] found that moxifloxacin can induce aortic aneurysms and clips by increasing bone bridging proteins in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Se encuentra en actual estudio con ratones, dentro de los cuales se han obtenido resultados alentadores frente a la inducción en células madre pluripotentes, sobre todo en los tipos de AME 1 y 2. Al posicionarse como posible tratamiento demuestra que se pueden descubrir nuevas terapias para enfermedades raras, enriqueciendo las opciones médicas, tanto como terapias independientes o para completar terapias que ya han sido usadas (22). Cas9.…”
Section: Moxifloxacinounclassified